Gold-catalyzed synthesis of 2,5-disubstituted oxazoles from carboxamides and propynals - Xu, Yun; Wang, Qian; Wu, Yufeng; Zeng, Zhongyi; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2019)
2,5-Disubstituted oxazoles are synthesized by oxidative gold catalysis. In contrast to a reported procedure that delivers 2,4-disubstituted oxazoles starting from terminal alkynes, a switch in selectivity towards a 2,5-disubstitution is achieved by the use of propynals as starting materials. In the new reaction, the key intermediate is formed by the nucleophilic attack of the carboxamide onto a gold carbenoid, and then condensates with the more electrophilic aldehyde moiety already present in the substrate and not with the ketone that is derived from the oxygen donor. This new cyclization mode introduces a new carbonyl moiety as substituent at the 2,5-disubstituted oxazole, an attractive motive that can be found in bioactive compounds or be used for further derivatizations.